Spatialisation de la biodiversité en Amazonie brésilienne pour appréhender l’influence de la colonisation des terres et des politiques publiques - Anne-Elisabeth Laques; Danielle Mitja; Eric Delaître; Marcelo Cordeiro Thales; Izildinha de Souza Miranda; Roberta de Fátima Rodrigues Coelho; Sandra Maria Neiva Sampaio (VertigO)
This article proposes a method for monitoring spatial dynamics of biodiversity which have occurred along the past 40 years ago in a farming community, Benfica, State of Pará, Brazilian Amazon. It is designed to assess "where", “when”, “why” changes have occurred, and "how much" surface is impacted. ? The goal is to help assess the impact of settlement policies on these dynamics. Data collected on both spatial disparities and rhythms of transformation should enrich knowledge on biodiversity evolution. In the current approach biodiversity is assessed by a scale of values resulting from several indicators combined. Each one contributes to estimate changes which occur during the land use change from forest to cropping. Biodiversity is then evaluated at two levels : one encountering the various forms of resources exploitation and attributing the measure of biodiversity to a landscape component (forest, fallow and crop / pasture) ; and the other, the category of actors (smallholders vs farmers), and reporting the extent of biodiversity to territory units which is preferentially operated. This monitoring process of this territory is easily replicable in time. In fact, it only depends on the availability of satellite images. This approach is on the process of validation to be used in further works dealing with similar anthropic forest regions.